Do institutions matter for entrepreneurial development? - Ruta Aidis (IZA World of Labor, 2023)
Governments foster conducive conditions for entrepreneurs through functioning free markets and good governance. In most post-Soviet countries, these conditions are still missing. Lack of political will combined with a detrimental Soviet legacy towards entrepreneurs continues to stunt entrepreneurship development. Some post-Soviet countries have initiated policies and programs to support entrepreneurship, reduce regulatory burden and provide resources and increased access to financing. However, these interventions are rarely combined with broader institutional reform so that their benefits are often limited or short lived.
Keywords: P2; D02; P5; 330; entrepreneurship; institutions; transition countries